Measurement properties of the Traumatic Brain Injury Quality of Life (TBI-QoL) and Spinal Cord Injury Quality of Life (SCI-QoL) measurement systems: a systematic review - Rebecca Ataman; Rehab Alhasani; Line Auneau-Enjalbert; Adria Quigley; Henry Ukachukwu Michael; Sara Ahmed (Systematic Reviews)
Abstract Purpose Traumatic brain injury and spinal cord injury impact all areas of individuals’ quality of life. A synthesis of available evidence for the Traumatic Brain Injury Quality of Life (TBI-QoL) and Spinal Cord Injury Quality of Life (SCI-QoL) measurement systems could inform evidence-based clinical practice and research. Thus, we aimed to systematically review the literature of existing evidence on the measurement properties of SCI-QoL and TBI-QoL among rehabilitation populations. Methods We used the COnsensus-based Standards for the selection of health Measurement Instruments (COSMIN) framework for evaluating measures to guide this systematic review. We searched nine electronic databases and registries, and hand-searched reference lists of included articles. Two independent reviewers screened selected articles and extracted the data. We used COSMIN’s thresholds to synthesize measurement properties evidence (insufficient, sufficient), and the modified GRADE approach to synthesize evidence quality (very-low, low, moderate, high). Results We included 16 studies for SCI-QoL and 14 studies for TBI-QoL. Both measurement systems have sufficient content validity, structural validity, internal consistency and construct validity across nearly all domains (GRADE: high). Most SCI-QoL domains and some TBI-QoL domains have sufficient evidence of cross-cultural validity and test–retest reliability (GRADE: moderate-high). Besides the cognition domains of TBI-QoL, which have indeterminate evidence for measurement error and sufficient evidence for responsiveness (GRADE: high), there is no additional evidence available for these measurement properties. Conclusion Rehabilitation researchers and clinicians can use SCI-QoL and TBI-QoL to describe and evaluate patients. Further evidence of measurement error, responsiveness, and predictive validity would advance the use and interpretation of SCI-QoL and TBI-QoL in rehabilitation.